Effects of matrix modification and bacteria amendment on the treatment efficiency of municipal tailwater pollutants by modified vertical flow constructed wetland. (1st March 2021) - Sun, Yaping; Zhou, Pincheng; Zhang, Nan; Zhang, Ze; Guo, Qingwei; Chen, Chengyu; Cui, Lihua
Abstract: Although vertical flow constructed wetland (VFCW) has great potentials for degradation of water contaminants, traditional VFCW has limited removal efficiencies for pollutants. This study constructed three sets of modified VFCW systems, including VFCW-A with matrix-modification using mixture of biochar and activated carbon, VFCW-B with microbial amendment using denitrifying bacteria, and VFCW-C with combined treatments of both. Their removal efficiencies for various pollutants in synthetic municipal tailwater were investigated. Results showed that the removal efficiencies for NH4 –N, NO3 –N, total nitrogen (TN), total phosphorus (TP), and chemical oxygen demand (COD) by VFCW-C were higher than VFCW-B throughout the experimental period, indicating that matrix-modification could improve the VFCW performance. The higher removal efficiencies for TN, TP, and COD by VFCW-C than VFCW-A also suggested the effectiveness of microbial amendment in VFCW. However, the improved removal for NO3 –N by VFCW-C over VFCW-A became less obvious at later operation stage due to insufficient carbon source. All three VFCWs achieved their best removal efficiency when carbon source was supplemented at CH3 COO − /TN ratio of 0.5. Our study suggested that the combined treatment of matrix-modification using biochar/activated carbon mixture and microbial amendment using denitrifying bacteria could effectively enhance the treatment efficiency of VFCW systems for tailwater pollutants from sewage plant. Graphical abstract: Image 1 Highlights: Three modified VFCWs were used to treat NH4 –N, NO3 –N, TN, TP, and COD in tailwater. Matrix-modification surpassed microbial amendment in single modified VFCW systems. VFCW-C with combined treatments performed better than single modified VFCW systems. VFCW-C removed 92.8%, 71.3%, 80.0%, 80.4% and 93.8% of five pollutants, respectively. All VFCWs performed the best when carbon source was supplemented at CH3 COO − /TN = 0.5.